TANGGUNG JAWAB NOTARIS DALAM PERSEKUTUAN PERDATA TERHADAP PEMBUATAN AKTA - Erika Kindyawati (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract __________________________________________________________________ Article 20, paragraph 1 of Law No. 2 Year 2014 on the Amendment of Law Number 30 Year 2004 on Notary, that notaries are allowed to run their office in the form of a civil partnership, in the sense of a shared office. The concept of shared office, limited to a notary together in one office, not in contact with the administration, accountability, as well as distribution of profits and losses. Notary needed, deed made understandable and acceptable to all parties requiring the certificate created and to have legal certainty. The purpose of this study was to determine the responsibility of the notary in a civil partnership to the deed. This research method using a kind of normative research with the approach of legislation (statue approach). Legal materials collection techniques using primary legal materials, secondary law, and tertiary legal materials. Furthermore, after legal materials collected then the legal materials were analyzed to obtain conclusions with content analysis techniques. The results showed that: first, notaries authorized officials to make the deed in the form of communion civil shall be responsible for the deed he made, the responsibility, among others, responsibility based UUJN, civil liability, liability in criminal liability under Notary code. That responsibility lies in each notary is not assigned, transferred or replaced to another notary joined in a civil union. Secondly, the legal consequences for the notary in a deed that can not carry out their duties in a responsible manner in the form of civil union that notaries may be subject to civil penalties, criminal or administrative if not pay attention to external aspects, material and formal in the manufacture aktanya. Key words: responsibility notaries, civil alliance, of deed       Abstrak Pasal 20 ayat 1 Undang-undang Nomor 2 Tahun 2014 Tentang Perubahan Atas Undang-undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris, bahwa notaris diperbolehkan menjalankan tugas jabatannya dalam bentuk persekutuan perdata, dalam arti kantor bersama. Konsep kantor bersama, sebatas notaris bersama-sama dalam satu kantor, tidak bersentuhan dengan pengurusan, pertanggungjawaban, maupun pembagian keuntungan dan kerugian. Notaris dibutuhkan, akta yang dibuat bisa dipahami dan diterima semua pihak yang menghendaki akta tersebut dibuat serta untuk memiliki kepastian hukum. Tujuan penelitian ini adalah untuk mengetahui tanggung jawab notaris dalam persekutuan perdata terhadap pembuatan akta. Metode penelitian ini menggunakan jenis penelitian normatif dengan pendekatan peraturan perundang-undangan (statue approach). Teknik pengumpulan bahan hukum menggunakan bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Selanjutnya setelah bahan hukum terkumpul maka bahan hukum tersebut dianalisis untuk mendapatkan konklusi dengan teknik content analysis. Hasil penelitian ini menunjukkan bahwa: pertama, notaris pejabat yang berwenang membuat akta dalam bentuk persekutuan perdata harus bertanggung jawab terhadap akta yang dibuatnya, tanggung jawab tersebut antara lain, tanggung jawab berdasarkan UUJN, tanggung jawab secara perdata, tanggung jawab secara pidana, tanggung jawab berdasarkan Kode Etik Notaris. Tanggung jawab tersebut terletak pada masing-masing notaris tidak dilimpahkan, dialihkan maupun digantikan kepada notaris lain yang tergabung dalam persekutuan perdata. Kedua, akibat hukum bagi notaris dalam membuat akta yang tidak dapat menjalankan tugasnya secara bertanggung jawab dalam bentuk persekutuan perdata bahwa notaris dapat dikenakan sanksi perdata, pidana maupun administrasi jika tidak memperhatikan aspek lahiriah, materiil dan formil dalam pembuatan aktanya.   Kata kunci: tanggungjawabnotaris, persekutuan perdata, akta notaris